CLIP-ACCORD: focus on full-dose combination - I. E. Chazova; L. G. Ratova (Кардиоваскулярная терапия и профилактика, 2006)
In CLIP-ACCORD study, 6000 patients from 21 cities of Russia, Ukraine, and Belorussia are participating. Aim. To study antihypertensive efficacy and safety of fixed-dose combination of enalapril and thiazide diuretic hydrochlorthiazide (Co-Renitec ®) among patients with arterial hypertension (AH) and high or very high risk of cardiovascular complications (CVC), in real-world clinical practice settings. Material and methods. CLIP-ACCORD is a multi-center, international, open prospective program. At present, 4224 AH patients (37% of males, 63% of females, aged 20-85 years; mean AH duration 8.4±7.6 (0-50) years) completed study protocol. The program included AH patients with high or very high CVD risk; antihypertensive therapy, if any, was ineffective. Co-Renitec® was administered once per day, at 8-10 AM. If target blood pressure (BP) level was achieved 4 weeks later, therapy in the same dose continued for another 8 weeks. Otherwise, Co-Renitec® dose was increased, and/or other antihypertensive agent was added. Full data were available for 4203 participants. Results. At baseline, BP was at Stage I AH level (National Cardiology Society classification, 2004) in 3% of patients; at Stage II level – in 67%; and at Stage III level – in 30%. After four-week Co-Renitec® treatment, complete BP normalization was achieved in 41% of participants, Stage I BP was registered in 40% of patients, Stage II – in 18%, and Stage III – in 1%. Co-Renitec® dose was increased in 26% of patients; other antihypertensive medications were added in 15%. After 12 weeks of Co-Renitec® treatment, target BP levels were achieved in 82% of patients. AH clinical symptoms improved in 98% of participants. After program end, 98% of participants continued CoRenitec® intake. Conclusion. Co-Renitec® antihypertensive therapy in AH patients with high and very high CVC risk was effective in full-dose combination, and facilitated target BP level achievement in 82% of patients.